PENDETEKSIAN SEL DARAH PUTIH DARI CITRA PREPARAT TANPA PEWARNAAN DENGAN FASTER R-CNN - oktaviana, oktaviana; Lina, Lina (Faculty of Information Technology, Universitas Tarumanagara, 2022)
Blood is a very important fluid in the human body. Blood consists of red blood cells (erythrocytes), white blood cells (leukocytes), blood platelets (platelets), and blood plasma. One of the important blood components for the human body is white blood cells, because they play a role in protecting the body from viruses, germs, and bacteria. In addition, by knowing the number of white blood cells in the human body, a person's health condition can be known. One way to count white blood cells is by using a peripheral blood smear. In the preparation of peripheral blood smears, staining will generally be carried out, which can increase the time, cost, and energy required. Technological developments, especially in the field of Computer Vision, are expected to help facilitate this process, so research is carried out in the detection of white blood cells from image preparations. In this study, detection will be carried out using Faster R-CNN method, combined with CLAHE and CIEL*a*b* color space for the pre-processing stage for unstained peripheral blood smear. The results of the tests carried out showed an accuracy rate of 98.61% for the stained peripheral blood smear and 86,67 % for the unstained peripheral blood smear.